Memori seorang jeneral Mohd Ghazali Haji Che Mat - Wan Hashim Haji Wan Teh; Ong, Jesica; Penerbit UPNM (Kuala Lumpur : Penerbit UPNM, 2017)
On biography of Mohd. Ghazali Haji Che Mat, a general in the armed forces of Malaysia.
Includes bibliographical references (page 151-152) and index.
In Malay.
Keywords: Mohd Ghazali Haji Che Mat; Malaysia. -- Tentera Darat -- History; Malaysia. -- Tentera Darat -- Biography; Generals -- Malaysia -- Biography; Soldiers -- Malaysia -- Biography; World War, 1939-1945 -- Malaysia; Malaysia -- History, Military